2021
DOI: 10.3389/fdmed.2021.765462
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamate-Based Histone Deacetylase Inhibitors as Potential Mediators to Induce Dentine Regeneration by Human Dental Pulp Cell

Abstract: Human dental pulp cells (hDPCs) have shown their plasticity when treated with the hydroxamate-based histone deacetylase (HDAC) inhibitor members, Trichostatin A (TSA), and suberoylanilide hydroxamic acid (SAHA). However, a comparison of their potency to stimulate odontoblast-like differentiation and mineralization has not been reported. The aim of our study was to confirm and compare these TSA and SAHA effects. Primary hDPCs cultured with/without various TSA or SAHA concentrations were evaluated using 3-(4,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…TSA is a potent pan-HDAC isoform inhibitor, non-selectively targeting various HDACs, which has garnered significant attention within dental pulp regenerative contexts [ 346 ]. TSA demonstrates significant anti-proliferative effects in primary DPCs when applied at 100 nM and 400 nM without affecting cell viability [ 347 , 348 ], reflecting previous reports using TSA at much lower concentrations [ 349 , 350 ]. Notably, TSA-induced caspase-3 and -9 cleavage were observed in DPSCs, a process associated with apoptosis [ 351 ].…”
Section: Epigenetic and Therapeutic Modulationsupporting
confidence: 69%
See 2 more Smart Citations
“…TSA is a potent pan-HDAC isoform inhibitor, non-selectively targeting various HDACs, which has garnered significant attention within dental pulp regenerative contexts [ 346 ]. TSA demonstrates significant anti-proliferative effects in primary DPCs when applied at 100 nM and 400 nM without affecting cell viability [ 347 , 348 ], reflecting previous reports using TSA at much lower concentrations [ 349 , 350 ]. Notably, TSA-induced caspase-3 and -9 cleavage were observed in DPSCs, a process associated with apoptosis [ 351 ].…”
Section: Epigenetic and Therapeutic Modulationsupporting
confidence: 69%
“…Discrepancies exist between studies regarding the effects of VPA on specific gene expression patterns due to variations in experimental methods and models. For instance, BMP-2 and DMP-1 upregulation was observed in VPA-treated primary DPCs under osteogenic induction [ 347 , 348 ], an effect which was not mirrored in non-induced MDPC-23 [ 353 ], underscoring the importance of representative experimental frameworks moving forward.…”
Section: Epigenetic and Therapeutic Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jin et al [35] reported that 50 nM increased growth, while 100 nM had a cytotoxic effect on DPSCs. On the contrary, Sulistyowati et al [36] reported that 200 nM TSA is an appropriate dose to treat DPCs in vitro without affecting their cell viability. Regarding VPA, a wide range of concentrations (0.01-100 mM) have been reported in human dental pulp cells [33,34,37] pointing out that higher VPA concentrations have an antiproliferative effect.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the increased pH values after immersion in simulated body fluid would help neutralize the acidic oral environment, where the bacteria damage teeth and the surrounding regions. 27 Various genes were involved in odontoblast-like cell differentiation and mineralization, namely the dentine remineralization and regeneration, 28 such as dentin matrix acidic phosphoprotein 1 (DSPP), dentin sialophosphoprotein (DSP), dentine matrix protein 1 (DMP-1), collagen type I alpha 1 chain (COL1A1), alkaline phosphatase (ALPL), integrin-binding sialoprotein (IBSP), bone gamma-carboxyglutamate protein (BGLAP), vascular endothelial growth factor A (VEGFA), cyclin dependent kinase inhibitor 1A (CDKN1A), etc . Additionally, GPC-1(glypican-1) and TGF-β1(transforming growth factor beta-1) have been reported to be related to the early stages of odontoblast-like cell differentiation, 29 with the downregulation of the GPC-1 gene observed for the formation of reparative dentine.…”
Section: Discussionmentioning
confidence: 99%